Environmental samples make soiled bedding sentinels dispensable for hygienic monitoring of IVC-reared mouse colonies. (June 2018) - Miller, Manuel; Brielmeier, Markus
Accurate knowledge of the health status of experimental animals is pivotal to high scientific and ethical standards in biomedical research. Individually ventilated cages (IVCs) are becoming the predominant system for housing laboratory mice, as they prevent cage-to-cage infections. However, this feature constitutes a major drawback for hygienic monitoring of mouse colonies, as traditional screening programs build on reliable transmission of infectious agents from experimental animals to sentinel mice commonly tested as representatives for the mouse colonies. In recent years, the laboratory animal community has realized that sentinels are ineffectual for screening mouse colonies in IVC systems because infections are often not transmitted to sentinels and therefore remain undetected. Furthermore, sentinel monitoring results in high numbers of used animals. In contrast, environmental monitoring provides a more reliable approach to identify and exclude pathogens in rodent colonies. In recent studies we provided evidence that polymerase chain reaction analysis of exhaust air particles is superior to soiled bedding sentinels for different agents. In this study, we show that testing pooled environmental samples generates more meaningful information compared to soiled bedding sentinels during routine hygienic monitoring in different barriers.